MENDARAH DAGINGKAN AL-QUR’AN - Zulfikar Ghazali (Cross-border, 2018)
The purpose of this study was to determine how the process of unite al-qur'an in blood and flesh in a person. This type of research is qualitative with literature review data sources. Meanwhile, this literature review is carried out in four stages consisting of: (1) searching for literature that is in accordance with the problem to be studied or researched by scanning the literature efficiently, using both manual and online methods, (2) assessing literature through a number of criteria, including the source itself, the author and the subject, (3) systematically examining and analyzing literature content, and (4) critically and deeply synthesizing literature content from literature such as the book or papers reviewed. For the research results, it can be seen that the Qur'an is one of the miracles and as the first revelation received by the Prophet. through the angel Gabriel. Al-Qur'an is also the culmination and closing of Allah's revelations for humans, and part of the pillars of faith, which was conveyed to the Prophet Muhammad. as a guide for humans in navigating life in the world. The Qur’an was revealed in three stages: first, the Qur’an was revealed by Allah to Lauh al-Mahfudz, second, the Qur’an was sent down from Lauh Mahfudz to Bait al-Izzah in the heavens of the world, and third, al- The Qur'an was revealed from Bayt al-Izzah to the Prophet Muhammad with the angel Jibril AS. Being ingrained in the Qur'an as a part of oneself can be done when a person is a child. Besides that, unite al-qur'an in blood and flesh is not only that the person must memorize the Qur'an, but all actions, behavior and speech must also reflect the Qur'an. Good ways of communicating and living socially have been taught in the Al-Qur'an. Patience sincerely. Tawakal (returning everything to Allah SWT.) When receiving a trial is a very heavy self-training process. If someone returns all his problems to Allah SWT. and always try to find a solution or a way to deal with these problems, and believe in the help of Allah SWT. in other words, remain warm to Allah SWT. in any condition, then that person will feel at ease, and spacious in his heart. In addition, this habit will give birth to a calm attitude both to the mind and heart, and reduce or even eliminate panic, which can make it easier for the person to find a way or solution in solving the problem that is or will be faced.